Sing of Cooperative Integrated Reading and Composition (CIRC) on English Reading Comprehension in Trsmm Class at Polnam - Leatemia*, Meiti; Frinaldi, Aldri (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
The Cooperative Integrated Reading and Composition (CIRC) method will be more attractive and increase students' achievement in English. The CIRC method can hone the cognitive level, affective, and psychomotor of students in spurring them to be creative based on the instructional guides that the lecture has given. This action research investigated reading comprehension in improving students' reading ability and composition. The participants of this study were 18 students in the second semester of TRSM class C Mechanical Department in the Academic year 2022/2023. Four stages of action research collected the data: Planning, action, observation, and reflection. Based on observation checklists, questionnaires, and tests as instruments, it has been proved that the students fulfilled the success criteria in the two cycles. Sixteen students, or 89% of the total number of students, got a score ranging from 65 to 100. On cycle 2, the average value of 84% of students fulfilled KKM (Passing Grade) with minimum standards, namely 75,00. The finding of this study is that the CIRC method can increase students' confidence, make them more relaxed and enjoyable, and motivate them to improve their reading comprehension ability.